Molecular Phenotyping of AR Signaling for Predicting Targeted Therapy in Castration Resistant Prostate Cancer - Hamid, Agus Rizal A. H.; Luna-Velez, Maria V.; Dudek, Aleksandra M.; Jansen, Cornelius F. J.; Smit, Frank; Aalders, Tilly W.; Verhaegh, Gerald W.; Schaafsma, Ewout; Sedelaar, John P. M.; Schalken, Jack A. (Frontiers in Oncology, 2021)
Castration-resistant prostate cancer (CRPC) is defined by resistance of the tumor to androgen deprivation therapy (ADT). Several molecular changes, in particular in the AR signaling cascade, have been described that may explain ADT resistance. The variety of changes may also explain why the response to novel therapies is so different in each patient. Testing the specific molecular changes may be a major step towards personalized treatment of CRPC patients. The aim of our study was to evaluate the molecular changes in the AR signaling cascade in CRPC patients. We have developed and validated several methods which are easy to use, and that require little tissue material, for exploring AR signaling pathway changes simultaneously. We found that the AR signaling pathway is still active in the majority of our CRPC patients, due to molecular changes in AR signaling components. There was heterogeneity in the molecular changes observed, but we could classify the patients in 4 major subgroups which are AR mutation, AR amplification, active intratumoral steroidogenesis, and combination of AR amplification and active intratumoral steroidogenesis.We suggest to characterize the AR signaling pathway in CRPC patients before starting any further treatment and a recent fresh tissue sample from the prostate or a metastatic site should be obtained for these characterization.